Regulating peracetic acid activation toward a singlet oxygen-dominated pathway via a 3D floating photothermal catalyst for selective antibiotic degradation - Qifan Wu; Cheuk Wai Lung; Jonathan J. Calvillo Solis; Yu Zhang; Musharib Khan; Ashutosh Kumar; Juhua He; Irene M.C. Lo (Chemical Engineering Journal, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Nanoplastics reprogram fungal metabolism to reshape extracellular microenvironments and manganese biomineralization - Chen Wu; Xinhong Qiu; Kazuya Tanaka; Yukinori Tani; Jonathan R. Lloyd; Qianqian Yu (Bioresource Technology, 2026)

Oral Language Skills of Children and Adolescents with Neurofibromatosis Type 1: a Systematic Review and Meta-analysis - Liyan Yu; Dan Liu; Jonathan M. Payne; Heather L. Thompson; Xian Wu; Julia Moreira; Lauren Morey; Michael Peper; Hannah Iroff; Benjamin F. Mujica; Yang Hou (Neuropsychology Review, 2026)

In situ polymerization of furfuryl alcohol for improved anode durability in aqueous Zn-ion batteries - Yuanyuan Guo; Goh Kim Wang Simon; Po-Ju Chiang; Kong Meng; Yu Zhe Lye; Jonathan Jeevan Singham; Chang Quan Lai (Chemical Engineering Journal, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Evaluation of the slope of inverse creatinine to define progressive chronic kidney disease in cats and associated risk factors - Pak-Kan Tang; Rosanne E. Jepson; Yu-Mei Chang; Jonathan Elliott (The Veterinary Journal, 2026)

Provena 2.0: Enabling provenance in operational modelling of reef restoration and adaptation interventions in the Great Barrier Reef - Jonathan Yu; Peter Baker; Linda Thomas; Ross Petridis; Jordan Munnerley; Peter Fitch; Sharon Tickell (Environmental Modelling & Software, 2026)

Next-generation strategies for PLA degradation: microbial consortia, metagenomics, enzyme engineering and AI-guided approaches - Avianto Rio Jonathan; Vignesh Kumar Balasubramanian; Shang-Tse Ho; Yen‑Po Chen; Pannida Khunnamwong; Jui-Yu Chou (Archives of Microbiology, 2026)

PDG_DB: A comprehensive database unveils environmental distribution patterns of plastic-degrading genes via large-scale multi-omic data analysis - Jiayu Zhang; Zuowu Zhang; Zehan Shen; Zehui Yu; Jiao Chen; Li Zeng; Dongyi Li; Xing Yan; Bing Li; Jonathan W.C. Wong (Water Research, 2026)

Dissolved organic matter enhances sunlight-induced transformation of tire rubber antioxidant 6PPD to 6PPD-quinone in aquatic environments - Minghan Zhu; Wenyan Yu; Zhujun Luo; Jonathan W.C. Wong; Shaoyu Tang; Zhen Yu; Zhi Dang; Junfeng Niu (Water Research, 2026)

Opportunities to enhance sugarcane yield and gross margin under climate change through irrigation and planting date adaptation - Shijin Yao; De Li Liu; Bin Wang; Siyi Li; Jonathan K. Webb; Keyu Xiang; Alfredo Huete; Lihong Wu; Hao Quan; Qiang Yu (Irrigation Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Quadriceps mitochondrial DNA quantity, quality, and gene expression after 2 years of calorie restriction: exploratory results from the CALERIE trial - Jayanta K. Das; Yu Zhang; Leanne M. Redman; Corby K. Martin; Sai Krupa Das; Susan B. Racette; Allen Herbst; Nianjun Liu; David B. Allison; Debbie McKenzie; Judd M. Aiken; Steve Horvath; et al. (GeroScience, 2026)
The Comprehensive Assessment of Long-term Effects of Reducing Intake of Energy (CALERIE)™ trial was a randomized, 2-year controlled trial of caloric restriction (CR) versus an ad libitum (AL) control condition in nonobese humans. We performed exploratory analyses of muscle mitochondrial DNA (mtDNA) integrity, one element of mitochondrial quality. Our aims were to assess the feasibility of this approach, explore associations to inform future hypotheses, estimate effect sizes and statistical power for subsequent studies, and contribute additional data to the CALERIE database. We used droplet digital PCR to quantitate the copy numbers of nuclear DNA, mtDNA, and mtDNA deletion mutations in remnant total DNA samples extracted from quadriceps biopsies at baseline ( n = 93), 12 months ( n = 44), and 24 months ( n = 31). MtDNA copy number and mutation frequency were correlated with existing gene expression data from the same muscle biopsies. MtDNA copy number was lower in females ( p = 0.0005) and declined over time ( p = 0.0001), with no statistically significant differences observed for CR versus AL ( p = 0.2898) or age across both groups ( p = 0.4644). Baseline copy number correlated positively with baseline physiological measures including fat-free mass ( r = 0.43, p = 2e−05), self-reported energy intake ( r = 0.34, p = 0.00077), resting metabolic rate ( r = 0.42, p = 0.00261), total energy expenditure ( r = 0.31, p = 0.00261), and V̇O₂max ( r = 0.41, p = 1e−04), and with gene expression related to mitochondrial function, while showing negative correlations with nuclear genome maintenance, RNA splicing, and ribosomes. MtDNA mutation frequency increased with age ( p = 0.0041) and showed a weak negative correlation with V̇O 2 max ( r = −0.23, p = 3e−05). MtDNA mutation frequency was not statistically different with CR. Mutation frequency was positively correlated with gene expression changes in inflammation and negatively correlated with protein translation. We observed that, as expected, mtDNA copy number declined over time, was lower in females, and correlated with metabolic measures and mitochondrial gene expression, suggesting its potential utility as a marker of metabolic health. These findings contribute to understanding mitochondrial adaptations to CR and highlight potential benefits of CR interventions. Graphical Abstract

Impact of temperature-stress synergistic effects on coal structural alignment - Song Yu; Geng Guorui; Feng Guangjun; Gao Jie; Veerle Vandeginste; Jonathan P. Mathews (Fuel, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Greenhouse gas emissions from black soldier fly composting of silver and silver sulfide nanoparticle-enriched sludge - Jingtao Wu; Lei Xiong; Yuantong Yang; Cui Li; Peng Mao; Qingqiu Zhou; Guangcan Yu; Xingyun Huang; Rajeshwar Dayal Tyagi; XinXing He; Jonathan W.C. Wong (Water Research, 2026)

Comparative genomic analysis of QTL for resistance to Aphanomyces euteiches between pea, lentil, faba bean, and the model species Medicago truncatula - Théo Leprévost; Baptiste Imbert; Clément Lavaud; Gilles Boutet; Henri Miteul; Antoine Leduc; Jonathan Kreplak; Ha-Trang Phung; Grégoire Aubert; Estefania Carrillo-Perdomo; Renan Uhdre; Hatice Sari; et al. (Theoretical and Applied Genetics, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Climate warming enhances sugarcane yield and increases annual harvest frequency in northern coastal New South Wales, Australia - Shijin Yao; De Li Liu; Bin Wang; Jonathan K. Webb; Siyi Li; Alfredo Huete; Keyu Xiang; Qiang Yu (Agricultural Systems, 2026)

Comparative Population Genomics of Relictual Caribbean Island Gossypium hirsutum - Weixuan Ning; Guanjing Hu; Daojun Yuan; Mark A. Arick; Chuan‐Yu Hsu; Zenaida V. Magbanua; Olga Pechanova; Daniel G. Peterson; Yating Dong; Joshua A. Udall; Corrinne E. Grover; Jonathan F. Wendel (Molecular Ecology, 2026)
Gossypium hirsutum is the world's most important source of cotton fibre, yet the diversity and population structure of its wild forms remain largely unexplored. The complex domestication history of G. hirsutum combined with reciprocal introgression with a second domesticated species, G. barbadense , has generated a wealth of morphological forms and feral derivatives of both species and their interspecies recombinants, which collectively are scattered across a large geographic range in arid regions of the Caribbean basin. Here we assessed genetic diversity within and among populations from two Caribbean islands, Puerto Rico ( n = 43, five sites) and Guadeloupe ( n = 25, one site), which contain putative wild or introgressed forms. Using whole‐genome resequencing data and a phylogenomic framework derived from a broader genomic survey, we parsed individuals into feral derivatives and truly wild forms. Feral cottons display uneven levels of genetic and morphological resemblance to domesticated cottons, with diverse patterns of genetic variation and heterozygosity. These patterns are inferred to reflect a complex history of interspecific and intraspecific gene flow that is spatially highly variable in its effects. Wild cottons in both Caribbean islands appear to be relatively inbred, especially the Guadeloupe samples. Our results highlight the dynamics of population demographics in relictual wild cottons that experienced profound genetic bottlenecks associated with repeated habitat destruction superimposed on a natural ecogeographical distribution comprising widely scattered populations. These results have implications for conservation and utilisation of wild diversity in G. hirsutum .

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Academic Achievement of Children and Adolescents with Neurofibromatosis Type 1: A Systematic Review and Meta-Analysis - Liyan Yu; Dan Liu; Jonathan M. Payne; Xian Wu; Heather L. Thompson; Julia Moreira; Lauren Morey; Benjamin Felipe Mujica; Yang Hou (Neuropsychology Review, 2025)

Unravelling the biosynthesis of phenylphenalenones: insights from metabolites and enzymes in Musella lasiocarpa - Hui Lyu; Lukas Ernst; Yoko Nakamura; Yu Okamura; Tobias G. Köllner; Katrin Luck; Benye Liu; Yu Chen; Ludger Beerhues; Jonathan Gershenzon; Christian Paetz (Phytochemistry Letters, 2025)

Gravel-bed river morphodynamic processes throughout a large flood with an 80-year return period from numerical modeling: Implications for flood regulation strategies - Qingcheng Yu; Colin D. Rennie; Jonathan M. Slaney (Journal of Hydrology, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Deep learning for wildfire risk prediction: Integrating remote sensing and environmental data - Zhengsen Xu; Jonathan Li; Sibo Cheng; Xue Rui; Yu Zhao; Hongjie He; Haiyan Guan; Aryan Sharma; Matthew Erxleben; Ryan Chang; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Visuospatial and Visuomotor Abilities of Individuals with Neurofibromatosis Type 1: A Systematic Review and Meta-analysis - Liyan Yu; Dan Liu; Jonathan M. Payne; Jing Zhang; Julia Moreira; Elora Shelly Mukhopadhyay; Angelena Novotney; Mary-Mac Chown; Joel Killam; Yang Hou (Neuropsychology Review, 2025)

Path planning algorithm for unmanned surface vessels based on COLREGs and Meta-TD3 - Xu Sun; Gangsheng Li; Zhaokai Liu; Ling Zhang; Haibo Yu; Dalei Song; Q.M. Jonathan Wu (Ocean Engineering, 2025)

A review of research on intelligent technology in building air conditioning system optimisation - Bo Li; Jonathan Chung Ee Yong; Lih Jiun Yu; Ezutah Udoncy Olugu; Xiaoqing Yang; Zhiming Zhang; Mohammed W Muhieldeen (International Journal of Refrigeration, 2025)

High spatial-resolution satellite mapping of suspended particulate matter in global coastal waters using particle composition-adaptive algorithms - Wenxiu Teng; Qian Yu; Dariusz Stramski; Rick A. Reynolds; Jonathan D. Woodruff; Brian Yellen (Remote Sensing of Environment, 2025)

Darriwilian radiolarians from slope facies sediments, Ordos Basin, North China and their paleoecological and paleogeographical implications - Xue-Jin Wu; Jia-Qi Song; Hui Luo; Yang Liu; Jonathan C. Aitchison; Yu-Jing Wang; Kui Yan; Zhong-Yang Chen; Di Chen; Yuan-Dong Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Molecular simulation of the potential effects of oxygen functionalities on the adsorption and diffusion of methane in kerogen - Guanwen Lu; Caineng Zou; Jonathan P. Mathews; Guosheng Zhang; Songqi Pan; Hanlin Liu; Yu Song; Yu Liu; Ganlin Hua; Zhengfu Zhao; Ming Yuan; Zhenhua Jing (Fuel, 2025)

Corrigendum to “Dynamics of wheat rhizosphere microbiome and its impact on grain production across growth stages” [964 (2025) 178524] - Mengwei Xu; Xu Liu; Tongyao Chen; Yige Zhao; Liya Ma; Xiaoyu Shi; Xiao Chen; Yu Shi; Jonathan M. Adams (Science of The Total Environment, 2025)

Dynamics of wheat rhizosphere microbiome and its impact on grain production across growth stages - Mengwei Xu; Xu Liu; Tongyao Chen; Yige Zhao; Liya Ma; Xiaoyu Shi; Xiao Chen; Yu Shi; Jonathan M. Adams (Science of The Total Environment, 2025)

Changes in enzyme activity, structure and growth strategies of the rhizosphere microbiome influenced by elevated temperature and CO2 - Bin Song; Yansheng Li; Zhenhua Yu; Jian Jin; Zihao Liu; Ruizhe Yang; Jonathan M. Adams; Bahar S. Razavi (Science of The Total Environment, 2024)

VOC emission rates from an indoor surface using a flux chamber and PTR-MS - Han N. Huynh; Jenna C. Ditto; Jie Yu; Michael F. Link; Dustin Poppendieck; Delphine K. Farmer; Marina E. Vance; Jonathan P.D. Abbatt (Atmospheric Environment, 2024)

Contributions of neighborhood physical and social environments to racial and ethnic disparities in birth outcomes in California: A mediation analysis - Shiwen Li; Lara J. Cushing; Roch A. Nianogo; Jonathan Liu; Rachel Connolly; Yu Yu; Michael Jerrett; Beate Ritz (Environmental Research, 2024)

Degradation and detoxification of 6PPD-quinone in water by ultraviolet-activated peroxymonosulfate: Mechanisms, byproducts, and impact on sediment microbial community - Wenyan Yu; Shaoyu Tang; Jonathan W.C. Wong; Zhujun Luo; Zongrui Li; Phong K. Thai; Minghan Zhu; Hua Yin; Junfeng Niu (Water Research, 2024)

Uppermost Darriwilian radiolarians from the lower part of Wulalike Formation, Northwest Ordos Basin, North China - Xue-Jin Wu; Zheng-Liang Huang; Hui Luo; Zheng-Hong Cai; Yao-Xuan Guo; Yang Liu; Yu-Jing Wang; Jonathan C. Aitchison; Yuan-Dong Zhang (Palaeoworld, 2024)

Degradation of tris(1,3-dichloro-2-propyl) phosphate (TDCPP) by ultraviolet activated hydrogen peroxide: Mechanisms, pathways and toxicity assessments - Zhujun Luo; Lizhu Yuan; Jonathan W.C. Wong; Minghan Zhu; Yuanyuan Yu; Kai Wang; Hua Yin; Shaoyu Tang; Junfeng Niu (Chemical Engineering Journal, 2024)

Quality control, safety assessment and preparation approaches of low molecular weight heparin - Yanlei Yu; Yue Song; Yunjie Zhao; Ningning Wang; Bin Wei; Robert J. Linhardt; Jonathan S. Dordick; Fuming Zhang; Hong Wang (Carbohydrate Polymers, 2024)

Assessing the future probable maximum precipitation in Utah under global warming - Hongping Gu; Jonathan Meyer; Shih‐Yu Simon Wang; Robert Gillies; Wei Zhang; Everett Taylor (International Journal of Climatology, 2024)
Probable maximum precipitation (PMP) has been an important criterion for designing hydrological infrastructure and it is likely to change with respect to global warming. To assess the potential risk that hydrological infrastructure in the U.S. state of Utah may encounter under the least mitigated emission scenario of Representative Concentration Pathway 8.5 (RCP8.5), this study identified historical (1950–2005) and future (2006–2100) PMP estimates to quantify the range and degree of change for extreme precipitation. The results show that an averaged RCP8.5 simulated 19.2% (3.43°C) increase in dewpoint temperature will result in a 39% (88.39 mm) increase in 24‐h 100‐mi 2 (259 km 2 ) PMP values. It is also found that the rapidly growing metropolitan areas of the state would experience a greater PMP increase (106.43 mm) than that in the state's National Parks and forested areas (93.98 mm). This discovery indicates a vulnerability that could affect both hydrological and metropolitan infrastructure. The planning of the state's infrastructure needs to consider the changing PMP under global warming.

Addressing Barriers and Facilitators to African Americans’ and Hispanics’ Participation in Clinical and Genomic Research Through a Bioethical Sensitive Video - Victoria Churchill; Yu-Mei Schoenberger; Vivian L. Carter; Jamirah Y. Chevrin; Windy Dean-Colomb; Roland Matthews; Desiree Rivers; Stephen O. Sodeke; Jonathan Ezer; Brian M. Rivers (Journal of Cancer Education, 2024)
Research advances on effective methods to prevent, diagnose, and treat cancer continue to emerge through clinical and genomic research. Most clinical trial and genomic research participants identify as White which limits the generalizability of research findings to non-White populations. With the development and access to technology, digital delivery of salient and tailored health education may provide innovative pathways to increase representation of African Americans (AA) and Hispanics in research. This project focused on the creation of a bioethical sensitive education video aimed at increasing participation in clinical trials and genomic research by bringing together experts from the community, healthcare, biomedical research, and public health. The goal was to utilize existing educational resources to create a tailored message to address AA/Hispanics’ beliefs, values, and bioethical concerns related to participation in clinical and genomic research. Models of behavior change and communication theories were leveraged to frame key components of the message, which then informed the framework for the animated video. Development of the video consisted of six iterative phases: 1) writing sessions; 2) storyboarding; 3) animating; 4) screening/revisions; 5) acceptability testing; 6) finalization. The final animated video is approximately 5 min in length and covers several topics including the goal of clinical research, disparities in research participation, bioethical concerns, and genomic research regulations. Increasing AA and Hispanic participation in clinical and genomic research is imperative to achieving health equity. Tailored messages via short videos may assist in addressing the barriers and facilitators towards research participation and increase intentions to enroll in trials.

Co–elevation of CO2 and temperature enhances nitrogen mineralization in the rhizosphere of rice - Jinyuan Zhang; Zhenhua Yu; Yansheng Li; Guanghua Wang; Xiaobing Liu; Caixian Tang; Jonathan Adams; Junjie Liu; Judong Liu; Shaoqing Zhang; Junjiang Wu; Jian Jin (Biology and Fertility of Soils, 2024)

Multiple processes jointly determine ecological uniqueness across forest plant life‐forms in Northeast China - Yue Chen; Jonathan A. Myers; Alejandro Ordonez; Jinghua Yu; Ji Ye; Fei Lin; Shuai Fang; Zikun Mao; Xugao Wang (Journal of Biogeography, 2024)
Aim Ecological uniqueness is an essential component of biodiversity. However, the mechanisms underlying patterns of ecological uniqueness remain unresolved. This study aims to assess the relative importance as well as interactive roles of four hypothesized processes (regional climate filtering, local environmental filtering, biotic heterogeneity and disturbance intensity [DI]) in shaping ecological uniqueness across three forest plant life‐forms (trees, shrubs and herbs) in a large temperate forest region. Location Northeast China. Methods We quantified ecological uniqueness as abundance and incidence‐based local relative contributions to beta diversity (i.e. LCBD indices) in the study region. Multiple beta regression analyses and piecewise structural equation models were used to determine the relative direct and interactive effects of four processes in shaping ecological uniqueness across forest plant life‐forms. Results The southern area of the region exhibited consistently greater LCBD values across plant life‐forms, highlighting its importance for conservation. All four processes jointly affected ecological uniqueness but their relative importance varied across plant life‐forms. Generally, regional climate had the dominant effect on tree LCBD while biotic heterogeneity was the most important process driving shrub and herb LCBDs. Local environmental filtering was less important in driving LCBD of all life‐forms. The significant direct effect of DI was only found in the herb group. Despite its weak direct effect, DI could indirectly shape tree and shrub LCBDs via biotic heterogeneity. Main Conclusions Our study suggests that current patterns of ecological uniqueness (i.e. LCBD) across forest plant life‐forms result from multiple processes, with regional climate filtering and biotic heterogeneity having the strongest effects on uniqueness patterns across all life‐forms. Meanwhile, DI is more critical for shaping ecological uniqueness of herbs than trees or shrubs. We highlight the interactive roles of biotic and abiotic filtering in shaping biologically distinct communities important for biodiversity conservation.

Higher trophic levels and species with poorer dispersal traits are more susceptible to habitat loss on island fragments - Zhonghan Wang; Jonathan M. Chase; Wubing Xu; Jinliang Liu; Donghao Wu; Aiying Zhang; Jirui Wang; Yuanyuan Luo; Mingjian Yu (Ecology, 2024)
Ongoing habitat loss and fragmentation caused by human activities represent one of the greatest causes of biodiversity loss. However, the effects of habitat loss and fragmentation are not felt equally among species. Here, we examined how habitat loss influenced the diversity and abundance of species from different trophic levels, with different traits, by taking advantage of an inadvertent experiment that created habitat islands from a once continuous forest via the creation of the Thousand Island Lake, a large reservoir in China. On 28 of these islands with more than a 9000‐fold difference in their area (0.12–1154 ha), we sampled plants, herbivorous insects, and predatory insects using effort‐controlled sampling and analyses. This allowed us to discern whether any observed differences in species diversity were due to passive sampling alone or to demographic effects that disproportionately influenced some species relative to others. We found that while most metrics of sampling effort‐controlled diversity increased with island area, the strength of the effect was exacerbated for species in higher trophic levels. When we more explicitly examined differences in species composition among islands, we found that the pairwise difference in species composition among islands was dominated by species turnover but that nestedness increased with differences in island area, indicating that some species are more likely to be absent from smaller islands. Furthermore, by examining trends of several dispersal‐related traits of species, we found that species with lower dispersal propensity tended to be those that were lost from smaller islands, which was observed for herbivorous and predatory insects. Our results emphasize the importance of incorporating within‐patch demographic effects, as well as the taxa and traits of species when understanding the influence of habitat loss on biodiversity.

Endophytic bacteria for Cd remediation in rice: Unraveling the Cd tolerance mechanisms of Cupriavidus metallidurans CML2 - Yuan Zhang; Qi Zhou; Chang Gao; Yue Lu; Yang Sheng; Ming Xiao; Yueli Yun; Jonathan Nimal Selvaraj; Xianhua Zhang; Yadong Li; Xuejing Yu (Journal of Hazardous Materials, 2024)

Health Disparities in the Aftermath of Flood Events: A Review of Physical and Mental Health Outcomes with Methodological Considerations in the USA - Aaron B. Flores; Jonathan A. Sullivan; Yilei Yu; Hannah K. Friedrich (Current Environmental Health Reports, 2024)

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

The effects of soil compaction on wheat seedling root growth are specific to soil texture and soil moisture status - Cailian Yu; Tinashe Mawodza; Brian S. Atkinson; Jonathan A. Atkinson; Craig J. Sturrock; Richard Whalley; Malcolm J. Hawkesford; Hannah Cooper; Xiaoxian Zhang; Hu Zhou; Sacha J. Mooney (Rhizosphere, 2024)

Toxic metal contamination effects mediated by hotspot intensity of soil enzymes and microbial community structure - Bin Song; Yue Xue; Zhenhua Yu; Yucheng He; Zihao Liu; Jie Fang; Yuchao Wang; Jonathan M. Adams; Youning Hu; Bahar S. Razavi (Journal of Hazardous Materials, 2024)

Corrigendum to “Structural transformations for a subbituminous coal, impact of temperature on gold-tube pyrolysis chars evaluated using HRTEM” [Fuel 311 (2022) 122581] - Wu Li; Yu Song; Wen-bin Yang; Jonathan P. Mathews (Fuel, 2024)

Environmental similarity is more important than distance in the community structuring processes of ammonia-oxidizing archaea in agricultural soils - Dorsaf KERFAHI; Yu SHI; Baozhan WANG; Hokyung SONG; Haiyan CHU; Jonathan M. ADAMS (Pedosphere, 2023)

Methane up-carbonizing: A way towards clean hydrogen energy? - Guoxing Chen; Xiao Yu; Kostya (Ken) Ostrikov; Bowen Liu; Jonathan Harding; Gert Homm; Heng Guo; Stephan Andreas Schunk; Ying Zhou; Xin Tu; Anke Weidenkaff (Chemical Engineering Journal, 2023)

Incorporating Uremic Solute-mediated Inhibition of OAT1/3 Improves PBPK Prediction of Tenofovir Renal and Systemic Disposition in Patients with Severe Kidney Disease - Shih-Yu Chang; Weize Huang; Alenka Chapron; Antonio J. López Quiñones; Joanne Wang; Nina Isoherranen; Danny D. Shen; Edward J. Kelly; Jonathan Himmelfarb; Catherine K. Yeung (Pharmaceutical Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

An attention-based multiscale transformer network for remote sensing image change detection - Wei Liu; Yiyuan Lin; Weijia Liu; Yongtao Yu; Jonathan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Wettability variation and its impact on CO2 storage capacity at the Wyoming CarbonSAFE storage hub: An experimental approach - Ying Yu; Sumaiya Farzana; Charles Nye; Davin Bagdonas; Prashant R. Waghmare; Zunsheng Jiao; Jonathan Fred McLaughlin (Fuel, 2023)

A new dimethylsulfoniopropionate lyase of the cupin superfamily in marine bacteria - Shu‐Yan Wang; Nan Zhang; Zhao‐Jie Teng; Xiao‐Di Wang; Jonathan D. Todd; Yu‐Zhong Zhang; Hai‐Yan Cao; Chun‐Yang Li (Environmental Microbiology, 2023)
Dimethylsulfoniopropionate (DMSP) is a marine organosulfur compound with important roles in stress protection, marine biogeochemical cycling, chemical signalling and atmospheric chemistry. Diverse marine microorganisms catabolize DMSP via DMSP lyases to generate the climate‐cooling gas and info‐chemical dimethyl sulphide. Abundant marine heterotrophs of the Roseobacter group (MRG) are well known for their ability to catabolize DMSP via diverse DMSP lyases. Here, a new DMSP lyase DddU within the MRG strain Amylibacter cionae H‐12 and other related bacteria was identified. DddU is a cupin superfamily DMSP lyase like DddL, DddQ, DddW, DddK and DddY, but shares dddU gene, mainly from Alphaproteobacteria , is widely distributed in the Atlantic, Pacific, Indian and polar oceans. For reference, dddU is less abundant than dddP , dddQ and dddK , but much more frequent than dddW , dddY and dddL in marine environments. This study broadens our knowledge on the diversity of DMSP lyases, and enhances our understanding of marine DMSP biotransformation.

Electroconductive and mechano-competent PUCL@CNT nanohybrid scaffolds guiding neuronal specification of neural stem/progenitor cells - Yu-Meng Li; Kapil D. Patel; Yoon-Koo Han; Suk-Min Hong; Yu-Xuan Meng; Hae-Hyoung Lee; Jeong Hui Park; Jonathan C. Knowles; Jung Keun Hyun; Jung-Hwan Lee; Hae-Won Kim (Chemical Engineering Journal, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

Abundant bacterial subcommunity is structured by a stochastic process in an agricultural system with P fertilizer inputs - Lei Liu; Li Zhu; Rong Yan; Yu Yang; Jonathan M. Adams; Jinshan Liu (Science of The Total Environment, 2023)

Corrigendum to “Vascular endothelium as a target for perfluroalkyl substances (PFAs)” [Environ. Res. 212 (2022) 1–4/11339] - Sharine Wittkopp; Fen Wu; Joseph Windheim; Morgan Robinson; Kurunthachalam Kannan; Stuart D. Katz; Yu Chen; Jonathan D. Newman (Environmental Research, 2023)

Stochasticity dominates assembly processes of soil nematode metacommunities on three Asian mountains - Shuqi ZOU; Jonathan ADAMS; Zhi YU; Nan LI; Dorsaf KERFAHI; Binu TRIPATHI; Changbae LEE; Teng YANG; Itumeleng MOROENYANE; Xing CHEN; Jinsoo KIM; Hyun Jeong KWAK; et al. (Pedosphere, 2023)

Greenhouse-gas forced changes in the Atlantic meridional overturning circulation and related worldwide sea-level change - Matthew P. Couldrey; Jonathan M. Gregory; Xiao Dong; Oluwayemi Garuba; Helmuth Haak; Aixue Hu; William J. Hurlin; Jiangbo Jin; Johann Jungclaus; Armin Köhl; Hailong Liu; Sayantani Ojha; et al. (Climate Dynamics, 2023)
The effect of anthropogenic climate change in the ocean is challenging to project because atmosphere-ocean general circulation models (AOGCMs) respond differently to forcing. This study focuses on changes in the Atlantic Meridional Overturning Circulation (AMOC), ocean heat content ( $$Δ$$ Δ OHC), and the spatial pattern of ocean dynamic sea level ( $$Δ ζ$$ Δ ζ ). We analyse experiments following the FAFMIP protocol, in which AOGCMs are forced at the ocean surface with standardised heat, freshwater and momentum flux perturbations, typical of those produced by doubling $$\hbox {CO}_{{2}}$$ CO 2 . Using two new heat-flux-forced experiments, we find that the AMOC weakening is mainly caused by and linearly related to the North Atlantic heat flux perturbation, and further weakened by a positive coupled heat flux feedback. The quantitative relationships are model-dependent, but few models show significant AMOC change due to freshwater or momentum forcing, or to heat flux forcing outside the North Atlantic. AMOC decline causes warming at the South Atlantic-Southern Ocean interface. It does not strongly affect the global-mean vertical distribution of $$Δ$$ Δ OHC, which is dominated by the Southern Ocean. AMOC decline strongly affects $$Δ ζ$$ Δ ζ in the North Atlantic, with smaller effects in the Southern Ocean and North Pacific. The ensemble-mean $$Δ ζ$$ Δ ζ and $$Δ$$ Δ OHC patterns are mostly attributable to the heat added by the flux perturbation, with smaller effects from ocean heat and salinity redistribution. The ensemble spread, on the other hand, is largely due to redistribution, with pronounced disagreement among the AOGCMs.

Soil microbial trait-based strategies drive the storage and stability of the soil carbon pool in Robinia pseudoacacia plantations - Min Zhang; Xiaoxiong Bai; Ying Wang; Yan Li; Yongxing Cui; Sile Hu; M. Adams Jonathan; Liguo Dong; Xuan Yu (CATENA, 2023)

Extended seasonal prediction of spring precipitation over the Upper Colorado River Basin - Siyu Zhao; Rong Fu; Michael L. Anderson; Sudip Chakraborty; Jonathan H. Jiang; Hui Su; Yu Gu (Climate Dynamics, 2023)
This study provides extended seasonal predictions for the Upper Colorado River Basin (UCRB) precipitation in boreal spring using an artificial neural network (ANN) model and a stepwise linear regression model, respectively. Sea surface temperature (SST) predictors are developed taking advantage of the correlation between the precipitation and SST over three ocean basins. The extratropical North Pacific has a higher correlation with the UCRB spring precipitation than the tropical Pacific and North Atlantic. For the ANN model, the Pearson correlation coefficient between the observed and predicted precipitation exceeds 0.45 ( p -value < 0.01) for a lead time of 12 months. The mean absolute percentage error (MAPE) is below 20% and the Heidke skill score (HSS) is above 50%. Such long-lead prediction skill is probably due to the UCRB soil moisture bridging the SST and precipitation. The stepwise linear regression model shows similar prediction skills to those of ANN. Both models show prediction skills superior to those of an autoregression model (correlation < 0.10) that represents the baseline prediction skill and those of three of the North American Multi-Model Ensemble (NMME) forecast models. The three NMME models exhibit different skills in predicting the precipitation, with the best skills of the correlation ~ 0.40, MAPE < 25%, and HSS > 40% for lead times less than 8 months. This study highlights the advantage of oceanic climate signals in extended seasonal predictions for the UCRB spring precipitation and supports the improvement of the UCRB streamflow prediction and related water resource decisions.

Do neighbourhood traffic-related air pollution and socio-economic status moderate the associations of the neighbourhood physical environment with cognitive function? Findings from the AusDiab study - Ester Cerin; Anthony Barnett; Yu-Tzu Wu; Erika Martino; Jonathan E. Shaw; Luke D. Knibbs; Govinda Poudel; Bin Jalaludin; Kaarin J. Anstey (Science of The Total Environment, 2023)

What is the role of disturbance in catalyzing spatial shifts in forest composition and tree species biomass under climate change? - Yu Liang; Eric J. Gustafson; Hong S. He; Josep M. Serra‐Diaz; Matthew J. Duveneck; Jonathan R. Thompson (Global Change Biology, 2023)
Mounting evidence suggests that climate change will cause shifts of tree species range and abundance (biomass). Abundance changes under climate change are likely to occur prior to a detectable range shift. Disturbances are expected to directly affect tree species abundance and composition, and could profoundly influence tree species spatial distribution within a geographical region. However, how multiple disturbance regimes will interact with changing climate to alter the spatial distribution of species abundance remains unclear. We simulated such forest demographic processes using a forest landscape succession and disturbance model (LANDIS‐II) parameterized with forest inventory data in the northeastern United States. Our study incorporated climate change under a high‐emission future and disturbance regimes varying with gradients of intensities and spatial extents. The results suggest that disturbances catalyze changes in tree species abundance and composition under a changing climate, but the effects of disturbances differ by intensity and extent. Moderate disturbances and large extent disturbances have limited effects, while high‐intensity disturbances accelerate changes by removing cohorts of mid‐ and late‐successional species, creating opportunities for early‐successional species. High‐intensity disturbances result in the northern movement of early‐successional species and the southern movement of late‐successional species abundances. Our study is among the first to systematically investigate how disturbance extent and intensity interact to determine the spatial distribution of changes in species abundance and forest composition.

Landslide-impacted soils recover faster biologically than chemically or physically, though recovery also varies with forest type in subtropical China - Jian Li; Lan Xiao; Jonathan D. Bakker; Qinghu Luo; Hang Yu; Jianzhao Wu; Songyang Li; Loretta Pedersen; Can Chen; Tao Hong; Han Lin; Daojie Wang; et al. (Soil and Tillage Research, 2023)

Stochastic processes dominate soil arbuscular mycorrhizal fungal community assembly along an elevation gradient in central Japan - Zihao Liu; Jie Fang; Bin Song; Ying Yang; Zhi Yu; Junli Hu; Ke Dong; Koichi Takahashi; Jonathan M. Adams (Science of The Total Environment, 2023)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Strong partitioning of soil bacterial community composition and co-occurrence networks along a small-scale elevational gradient on Zijin Mountain - Xu Liu; Teng Yang; Yu Shi; Yichen Zhu; Mulin He; Yunke Zhao; Jonathan M. Adams; Haiyan Chu (Soil Ecology Letters, 2021)

SOX9-induced Generation of Functional Astrocytes Supporting Neuronal Maturation in an All-human System - Katrien Neyrinck; Johanna Van Den Daele; Tim Vervliet; Jonathan De Smedt; Keimpe Wierda; Melissa Nijs; Tom Vanbokhoven; Astrid D’hondt; Mélanie Planque; Sarah-Maria Fendt; Pei-Yu Shih; Frederik Seibt; et al. (Stem Cell Reviews and Reports, 2021)
Astrocytes, the main supportive cell type of the brain, show functional impairments upon ageing and in a broad spectrum of neurological disorders. Limited access to human astroglia for pre-clinical studies has been a major bottleneck delaying our understanding of their role in brain health and disease. We demonstrate here that functionally mature human astrocytes can be generated by SOX9 overexpression for 6 days in pluripotent stem cell (PSC)-derived neural progenitor cells. Inducible (i)SOX9-astrocytes display functional properties comparable to primary human astrocytes comprising glutamate uptake, induced calcium responses and cytokine/growth factor secretion. Importantly, electrophysiological properties of iNGN2-neurons co-cultured with iSOX9-astrocytes are indistinguishable from gold-standard murine primary cultures. The high yield, fast timing and the possibility to cryopreserve iSOX9-astrocytes without losing functional properties makes them suitable for scaled-up production for high-throughput analyses. Our findings represent a step forward to an all-human iPSC-derived neural model for drug development in neuroscience and towards the reduction of animal use in biomedical research. Graphical Abstract

Global patterns and drivers of alpine plant species richness - Riccardo Testolin; Fabio Attorre; Peter Borchardt; Robert F. Brand; Helge Bruelheide; Milan Chytrý; Michele De Sanctis; Jiri Dolezal; Manfred Finckh; Sylvia Haider; Andreas Hemp; Ute Jandt; et al. (Global Ecology and Biogeography, 2021)
Aim Alpine ecosystems differ in area, macroenvironment and biogeographical history across the Earth, but the relationship between these factors and plant species richness is still unexplored. Here, we assess the global patterns of plant species richness in alpine ecosystems and their association with environmental, geographical and historical factors at regional and community scales. Location Global. Time period Data collected between 1923 and 2019. Major taxa studied Vascular plants. Methods We used a dataset representative of global alpine vegetation, consisting of 8,928 plots sampled within 26 ecoregions and six biogeographical realms, to estimate regional richness using sample‐based rarefaction and extrapolation. Then, we evaluated latitudinal patterns of regional and community richness with generalized additive models. Using environmental, geographical and historical predictors from global raster layers, we modelled regional and community richness in a mixed‐effect modelling framework. Results The latitudinal pattern of regional richness peaked around the equator and at mid‐latitudes, in response to current and past alpine area, isolation and the variation in soil pH among regions. At the community level, species richness peaked at mid‐latitudes of the Northern Hemisphere, despite a considerable within‐region variation. Community richness was related to macroclimate and historical predictors, with strong effects of other spatially structured factors. Main conclusions In contrast to the well‐known latitudinal diversity gradient, the alpine plant species richness of some temperate regions in Eurasia was comparable to that of hyperdiverse tropical ecosystems, such as the páramo. The species richness of these putative hotspot regions is explained mainly by the extent of alpine area and their glacial history, whereas community richness depends on local environmental factors. Our results highlight hotspots of species richness at mid‐latitudes, indicating that the diversity of alpine plants is linked to regional idiosyncrasies and to the historical prevalence of alpine ecosystems, rather than current macroclimatic gradients.

Integrated metabolomics reveals altered lipid metabolism in adipose tissue in a model of extreme longevity - Justin Darcy; Yimin Fang; Samuel McFadden; Matthew D. Lynes; Luiz O. Leiria; Jonathan M. Dreyfuss; Valerie Bussburg; Vladimir Tolstikov; Bennett Greenwood; Niven R. Narain; Michael A. Kiebish; Andrzej Bartke; et al. (GeroScience, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Occurrence, composition and biological risk of organophosphate esters (OPEs) in water of the Pearl River Estuary, South China - Yongfeng Shi; Ying Zhang; Yongming Du; Deguan Kong; Qihang Wu; Yiguo Hong; Yu Wang; Nora F.Y. Tam; Jonathan Y.S. Leung (Environmental Science and Pollution Research, 2020)

Transplantation of stem cells from umbilical cord blood as therapy for type I diabetes - Rachel Stiner; Michael Alexander; Guangyang Liu; Wenbin Liao; Yongjun Liu; Jingxia Yu; Egest J. Pone; Weian Zhao; Jonathan R. T. Lakey (Cell and Tissue Research, 2019)

Proceedings of the fourth international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Christine B. Ambrosone; Reiko Nishihara; Hugo J. W. L. Aerts; Melissa Bondy; Nilanjan Chatterjee; Montserrat Garcia-Closas; Marios Giannakis; Jeffrey A. Golden; Yujing J. Heng; N. Sertac Kip; Jill Koshiol; et al. (Cancer Causes & Control, 2019)

A biogeographic map of soil bacterial communities in wheats field of the North China Plain - Yu Shi; Yuntao Li; Meiqing Yuan; Jonathan M. Adams; Xianzhang Pan; Yunfeng Yang; Haiyan Chu (Soil Ecology Letters, 2019)

Assessing aerosol indirect effect on clouds and regional climate of East/South Asia and West Africa using NCEP GFS - Huilin Huang; Yu Gu; Yongkang Xue; Jonathan Jiang; Bin Zhao (Climate Dynamics, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Reduction in Cannabis Use and Functional Status in Physical Health, Mental Health, and Cognition - Larissa J. Mooney; Yuhui Zhu; Caroline Yoo; Jonathan Valdez; Kevin Moino; Jung-Yu Liao; Yih-Ing Hser (Journal of Neuroimmune Pharmacology, 2018)

A Simplified Irrigation Pump Testing Method for Developing Countries: A Case Study in Bangladesh - Su Yu; Jonathan S. Colton; Md. Abdul Matin; Timothy J. Krupnik (Irrigation and Drainage, 2018)
Much of South Asia experiences a monomodal rainfall pattern with a distinct dry season following the annual monsoon. Enabling irrigation during the dry season has therefore been crucial in assuring improved productivity and double‐cropping. This is particularly the case in southern Bangladesh, where recent government initiatives have called for an expansion of surface water irrigation to reduce pressure on groundwater tables in intensively cultivated areas in the north of the country, where dry season boro rice is grown. This paper describes a method based on first principles of fluid mechanics to characterize the performance of surface water irrigation pumps used by small‐scale farmers in South Asia and Bangladesh. This method is unique, as it incorporates an optimized protocol suitable for resource‐limited conditions found in many developing countries and provides a comprehensive yet simple‐to‐use pump selection method for surface water irrigation pump customers. Using pump impellers as a case study, the method also characterizes the effect of pump geometric variations resulting from the variable production and assembly practices found in different manufacturing workshops. This method was validated with a case study in Bangladesh supported by both full‐scale field testing and numerical simulation results. © 2018 The Authors. Irrigation and Drainage published by John Wiley & Sons Ltd on behalf of International Commission for Irrigation and Drainage

Prediction of metabolism-induced hepatotoxicity on three-dimensional hepatic cell culture and enzyme microarrays - Kyeong-Nam Yu; Sashi Nadanaciva; Payal Rana; Dong Woo Lee; Bosung Ku; Alexander D. Roth; Jonathan S. Dordick; Yvonne Will; Moo-Yeal Lee (Archives of Toxicology, 2018)

How disturbance, competition, and dispersal interact to prevent tree range boundaries from keeping pace with climate change - Yu Liang; Matthew J. Duveneck; Eric J. Gustafson; Josep M. Serra‐Diaz; Jonathan R. Thompson (Global Change Biology, 2018)
Climate change is expected to cause geographic shifts in tree species' ranges, but such shifts may not keep pace with climate changes because seed dispersal distances are often limited and competition‐induced changes in community composition can be relatively slow. Disturbances may speed changes in community composition, but the interactions among climate change, disturbance and competitive interactions to produce range shifts are poorly understood. We used a physiologically based mechanistic landscape model to study these interactions in the northeastern United States. We designed a series of disturbance scenarios to represent varied disturbance regimes in terms of both disturbance extent and intensity. We simulated forest succession by incorporating climate change under a high‐emissions future, disturbances, seed dispersal, and competition using the landscape model parameterized with forest inventory data. Tree species range boundary shifts in the next century were quantified as the change in the location of the 5th (the trailing edge) and 95th (the leading edge) percentiles of the spatial distribution of simulated species. Simulated tree species range boundary shifts in New England over the next century were far below (usually

Co-altered functional networks and brain structure in unmedicated patients with bipolar and major depressive disorders - Hao He; Jing Sui; Yuhui Du; Qingbao Yu; Dongdong Lin; Wayne C. Drevets; Jonathan B. Savitz; Jian Yang; Teresa A. Victor; Vince D. Calhoun (Brain Structure and Function, 2017)

Environment and geographic distance differ in relative importance for determining fungal community of rhizosphere and bulk soil - Kaoping Zhang; Jonathan M. Adams; Yu Shi; Teng Yang; Ruibo Sun; Dan He; Yingying Ni; Haiyan Chu (Environmental Microbiology, 2017)
Summary Rhizospheric fungi play major roles in both natural and agricultural ecosystems. However, little is known about the determinants of their diversity and biogeographic patterns. Here, we compared fungal communities in rhizosphere and bulk soils of wheat fields in the North China Plain. The rhizosphere had a lower fungal diversity (observed OTUs and Chao1) than bulk soil, and a distinct fungal community structure in rhizosphere compared with bulk soil. The relative importance of environmental factors and geographic distance for fungal distribution differed between rhizosphere and bulk soil. Environmental factors were the primary cause of variations in total fungal community and major fungal phyla in bulk soil. By contrast, fungal communities in soils loosely attached to roots were predictable from both environmental factors and influences of geographic distance. Communities in soils tightly attached to roots were mainly determined by geographic distance. Our results suggest that both contemporary environment processes (present‐day abiotic and biotic environment characters) and historical processes (spatial isolation, dispersal limitation occurred in the past) dominate variations of fungal communities in wheat fields, but their relative importance of all these processes depends on the proximity of fungal community to the plant roots.

Evaluation of MODIS land surface temperature with in-situ snow surface temperature from CREST-SAFE - Carlos L. Pérez-Díaz; Tarendra Lakhankar; Peter Romanov; Jonathan Muñoz; Reza Khanbilvardi; Yunyue Yu (International Journal of Remote Sensing, 2017)

Discovery and characterization of two new stem rust resistance genes in Aegilops sharonensis - Guotai Yu; Nicolas Champouret; Burkhard Steuernagel; Pablo D. Olivera; Jamie Simmons; Cole Williams; Ryan Johnson; Matthew J. Moscou; Inmaculada Hernández-Pinzón; Phon Green; Hanan Sela; Eitan Millet; et al. (Theoretical and Applied Genetics, 2017)

Improved delivery of Cas9 protein/gRNA complexes using lipofectamine CRISPRMAX - Xin Yu; Xiquan Liang; Huimin Xie; Shantanu Kumar; Namritha Ravinder; Jason Potter; Xavier de Mollerat du Jeu; Jonathan D. Chesnut (Biotechnology Letters, 2016)

Treatment with Trehalose Prevents Behavioral and Neurochemical Deficits Produced in an AAV α-Synuclein Rat Model of Parkinson’s Disease - Qing He; James B. Koprich; Ying Wang; Wen-bo Yu; Bao-guo Xiao; Jonathan M. Brotchie; Jian Wang (Molecular Neurobiology, 2016)

Bacterial community dissimilarity between the surface and subsurface soils equals horizontal differences over several kilometers in the western Tibetan Plateau - Haiyan Chu; Huaibo Sun; Binu M. Tripathi; Jonathan M. Adams; Rong Huang; Yangjian Zhang; Yu Shi (Environmental Microbiology, 2016)
Summary Many studies have investigated patterns in the near‐surface soil microbial community over large spatial scales. However, less is known about variation in subsurface (15–30 cm of depth) microbial communities. Here we studied depth profiles of microbial communities in high‐elevation soils from Tibet. The relative abundance of Acidobacteria, Chloroflexi and Alphaproteobacteria was higher in near‐surface layers, while the relative abundance of Actinobacteria, Gemmatimonadetes and Betaproteobacteria was higher in the subsurface samples. The microbial community structure was distinct between the surface and subsurface soil layers, strongly correlating with variation in total carbon (TC) and carbon to nitrogen ratio (C/N). The differences in the microbial community between the layers were about the same as the horizontal differences between sites separated by many kilometers. Overall, we found that TC and C/N were the best predictors for both surface and subsurface microbial community distribution. Exploration of the relative contribution of distance and environmental variables to community composition suggests that the contemporary environment is the primary driver of microbial distribution in this region. Reflecting niche conservatism in evolution, the microbial communities in each soil site and layer tended to be more phylogenetically clustered than expected by chance, and surface soil layer samples were more likely to be clustered than subsurface samples.

Differential modulation of methamphetamine-mediated behavioral sensitization by overexpression of Mu opioid receptors in nucleus accumbens and ventral tegmental area - Chi-Chung Kuo; Hui Shen; Brandon K. Harvey; Seong-Jin Yu; Theresa Kopajtic; Josh. J. Hinkle; Stephanos Kyrkanides; Jonathan L. Katz; Yun Wang (Psychopharmacology, 2016)

Extraction of power-transmission lines from vehicle-borne lidar data - Haiyan Guan; Yongtao Yu; Jonathan Li; Zheng Ji; Qi Zhang (International Journal of Remote Sensing, 2016)

Characterization of a genetic and antigenic variant of avian paramyxovirus 6 isolated from a migratory wild bird, the red-necked stint (Calidris ruficollis) - Vuong Nghia Bui; Tetsuya Mizutani; Tung Hoang Nguyen; Dai Quang Trinh; Sanaa S. A. Awad; Germaine L. Minoungou; Yu Yamamoto; Kikuyasu Nakamura; Keisuke Saito; Yukiko Watanabe; Jonathan Runstadler; Falk Huettmann; et al. (Archives of Virology, 2014)

DEM generation from lidar data in wooded mountain areas by cross-section-plane analysis - Haiyan Guan; Jonathan Li; Yongtao Yu; Liang Zhong; Zheng Ji (International Journal of Remote Sensing, 2014)

Antimicrobial activity in the egg wax of the tick Amblyomma hebraeum (Acari: Ixodidae) is associated with free fatty acids C16:1 and C18:2 - Zhijun Yu; Euan L. S. Thomson; Jingze Liu; Jonathan J. Dennis; René L. Jacobs; W. Reuben Kaufman (Experimental and Applied Acarology, 2012)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Opacification of Shape Memory Polymer Foam Designed for Treatment of Intracranial Aneurysms - Jennifer N. Rodriguez; Ya-Jen Yu; Matthew W. Miller; Thomas S. Wilson; Jonathan Hartman; Fred J. Clubb; Brandon Gentry; Duncan J. Maitland (Annals of Biomedical Engineering, 2012)

Use of standard vocabulary services in validation of water resources data described in XML - Jonathan Yu; Simon Cox; Gavin Walker; Paul J. Box; Paul Sheahan (Earth Science Informatics, 2011)

Exquisite binding specificity of Sclerotium rolfsii lectin toward TF-related O-linked mucin-type glycans - Vishwanath B. Chachadi; Shashikala R. Inamdar; Lu-Gang Yu; Jonathan M. Rhodes; Bale M. Swamy (Glycoconjugate Journal, 2011)

An fMRI Study of the Differences in Brain Activity During Active Ankle Dorsiflexion and Plantarflexion - Jonathan P. Trinastic; Steven A. Kautz; Keith McGregor; Chris Gregory; Mark Bowden; Michelle B. Benjamin; Marc Kurtzman; Yu Ling Chang; Tim Conway; Bruce Crosson (Brain Imaging and Behavior, 2010)

Identifying Change-Points in Biological Sequences via Sequential Importance Sampling - George Yu. Sofronov; Gareth E. Evans; Jonathan M. Keith; Dirk P. Kroese (Environmental Modeling & Assessment, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Altered glycosylation in inflammatory bowel disease: A possible role in cancer development - Barry J. Campbell; Lu-Gang Yu; Jonathan M. Rhodes (Glycoconjugate Journal, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Pyruvate oxidation by Methanococcus spp. - Yu-Ling Yang; Jonathan Ladapo; William B. Whitman (Archives of Microbiology, 1992)